Tension-free transobturator vaginal tape and autologous rectus fascia transobturator vaginal sling for the treatment of urinary stress incontinence: a prospective clinical study - Elsersy, Mervat A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: A large proportion of adult women complain of urinary incontinence, which has considerable drawbacks on their quality of life and social incorporation in the community. Conservative measures had been tried for several decades but with limited efficacy in huge proportion of patients. Vaginal sling procedures, since it was introduced in medical field had achieved good success rates with low complication rates. However, they still cause problems. Since Ulmsten introduced the tension-free vaginal tape in 1995, it has become a popular method for surgical treatment of urodynamically proven USI. In this study, we are going to compare between tension-free Trans obturator vaginal tape (TVT-O) using synthetic polypropylene macro porous monoﬁlament mesh and autologous rectus fascia Trans obturator sling. Methods: 80 patients had stress urinary incontinence were randomly assigned to either group (1) who underwent insertion of synthetic tension free vaginal tape using (Aris- Transobturator Sling System) or group to (2) to whom autologous rectus fascia transobturator vaginal sling was applied. Results: Objective and subjective cure rates were comparable in both groups, but patients in group (1) had shorter operative time and less duration of post-operative catheterization. Patients in group (1) were statistically more satisfied than patients in group (2). Conclusions: Both techniques are effective in the treatment of female stress incontinence